Computer science students simulation in capturing tacit knowledge by using NGT for reducing traffic jam - Andretti Abdillah, Leon; Novita Sari, Ifit; Eka Indriani, Dian (International Journal of Engineering and Technology, 2018)
The subject knowledge management systems is one of the main courses in information systems study program, faculty of computer science. This course is offered at A concentration for students in semester 5 (five). Knowledge consists of knowledge explicit and tacit. To capture tacit knowledge, it can be done by involving a number of methods, namely: 1) Brainstorming, and 2) Nominal Group Technique. The study also involves a number of social information technologies, such as: 1) Facebook, 2) WordPress, 3) DropBox, and 4) YouTube. The topic for the theme of knowledge is how to reduce traffic jam. After passing 2 (two) simulation rounds, this research get 8 (eight) ideas suggestion related to vehicle parking in an effort to reduce traffic jam. The tacit knowledge capture simulation with NGT is able to provide acceptable suggestions by all the panelists involved. The use of social information technology in this study also received a very good response from the panelists.Â Â